Family Involvement in Decisions to Forego or Withdraw Dialysis: A Qualitative Study of Nephrologists in the United States and England - Vanessa Grubbs; Delphine S. Tuot; Neil R. Powe; Donal O’Donoghue; Catherine A. Chesla (Kidney Medicine, 2019)
Background: Shared decision making may be particularly complex for the older patient with end-stage renal disease (ESRD), in part because of family involvement. Nephrologists’ perspectives on the family’s role in ESRD decision making have not been explored. Study Design: Semi-structured, individual, qualitative interviews. Setting & Participants: Practicing US and English adult nephrologists. Methodology: Participants were purposively sampled based on age, race, sex, geographic location, and practice type. Each was asked about his or her perspectives and experiences related to foregoing and withdrawing dialysis therapy. Analytical Approach: Interviews were audiotaped, transcribed, and analyzed using narrative and thematic analysis. Results: We conducted 59 semi-structured interviews with nephrologists from the United States (n = 41) and England (n = 18). Most participants were 45 years or younger, men, and white. Average number of years since completing nephrology training was 14.2 (SD, 11.6). Nephrologists in both countries identified how patients’ families may act to facilitate or impede decisions to forego and withdraw dialysis therapy, which fell within the following subthemes: (1) emotional response to decision making, (2) involvement in patient health care/awareness of illness, (3) trust in physician, and (4) acceptance of patient wishes. Only US nephrologists raised families’ financial dependence on patients as an impediment to foregoing or withdrawing dialysis therapy. Limitations: Participants’ views may not fully capture those of all US or English nephrologists. Conclusions: Nephrologists in the United States and England identified several ways that patients’ families help and hinder ESRD decision making in keeping with patient prognosis and preferences. Nephrologists should hone their communication skills to better navigate these interactions. Index Words: Family, dialysis withdrawal, foregoing dialysis, qualitative methodology, conservation management, ESRD decision-making